PENGARUH MEDIA PEMBELAJARAN PAPAN MUSI DENGAN MODEL KOOPERATIF TIPE NHT TERHADAP HASIL BELAJAR MATEMATIKA MATERI KPK DAN FPB PADA SISWA KELAS V SDN BANGKELEKILA - Tangdialla, Jaya; S Situru, Roberto; Laen Langi, Weryanti (Al-mujahidah, 2025)
. This study aims to determine the effect of using the Multi-Function Learning Media (Papan Musi) with the Numbered Heads Together (NHT) cooperative learning model on the mathematics learning outcomes of fifth-grade students at SDN 3 Bangkelekila’ in the topics of Least Common Multiple (LCM) and Greatest Common Factor (GCF). The study uses a quantitative method with a quasi-experimental design, involving two classes: the experimental class using Papan Musi media and the control class using conventional learning methods. Data was collected through pretest and posttest, followed by analysis using normality, homogeneity tests, and hypothesis testing (t-test). The results show that the use of Papan Musi media with the NHT model significantly affects the improvement of student learning outcomes. The posttest scores of the experimental class using Papan Musi were higher (average 90.00) compared to the control class (average 74.75), with a t-test significance value of 0.000 (p < 0.05). Therefore, it can be concluded that Papan Musi media is more effective in enhancing students' understanding of LCM and GCF.